Design of a prospective, multicenter, and cohort study of an innovative electromagnetic navigation bronchoscopy in diagnosing pulmonary nodules among Chinese population - Xie, Fangfang (J Thorac Dis, 2019)
Electromagnetic navigation bronchoscopy (ENB) has been demonstrated to increase the diagnostic yield of peripheral pulmonary lesions. We designed two prospective clinical trials using an innovative ENB system that can combine with both thick and thin bronchoscope, including a randomized controlled clinical study to assess the usefulness of the ENB system and a real-world study to explore the optimal way to use this system. Patients with peripheral pulmonary nodules (PPNs) suspicious of lung cancer with the long diameter more than 8 mm and no more than 30 mm will be enrolled in the study. A total of 400 patients will be enrolled in the randomized controlled clinical study and randomly divided into two groups, endobronchial ultrasound (EBUS) combined with guide sheath (GS) with or without ENB. The real-world study is a single arm and observational study, at least 750 subjects will be enrolled in the study. ENB combined with or without other guided bronchoscopy techniques, fluoroscopy, and rapid on-site cytologic evaluation (ROSE) will be performed according to the judgment of the operator. The primary endpoint of the two studies is the diagnostic yield of ENB in diagnosing PPNs. The secondary endpoint includes the diagnostic yields for malignant and benign diseases, navigation time, time for finding lesions, total operation time, complication rate, etc. Enrollment for the study began in July 2018 and is currently in progress. With up to 1,150 subjects estimated to be enrolled, the study will provide evidence on the usage of the novel ENB system in diagnosing PPNs.